2011
DOI: 10.1371/journal.pone.0028903
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Stabilization of Expanding Aortic Aneurysms by a Short Course of Cyclosporine A through Transforming Growth Factor-Beta Induction

Abstract: Abdominal aortic aneurysms (AAAs) expand as a consequence of extracellular matrix destruction, and vascular smooth muscle cell (VSMC) depletion. Transforming growth factor (TGF)-beta 1 overexpression stabilizes expanding AAAs in rat. Cyclosporine A (CsA) promotes tissue accumulation and induces TGF -beta1 and, could thereby exert beneficial effects on AAA remodelling and expansion. In this study, we assessed whether a short administration of CsA could durably stabilize AAAs through TGF-beta induction. We showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 36 publications
4
48
1
Order By: Relevance
“…34,35 Consistent with our findings on the role of mtROS in AIIinduced activation of the NLRP3 inflammasome, Zhou et al 18 and Nakahira et al 19 recently showed the mitochondria to be the major source of ROS, which activates the inflammasome. Interestingly, Dai et al 36 reported that administration of cyclosporin A protects AAA expansion in the rat elastase and murine calcium chloride models in vivo. Although molecular link between mitochondrial dysfunction and inflammasome activation remains to be determined, these data suggest the critical role of mitochondria-dependent NLRP3 inflammasome activation in progression of AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Consistent with our findings on the role of mtROS in AIIinduced activation of the NLRP3 inflammasome, Zhou et al 18 and Nakahira et al 19 recently showed the mitochondria to be the major source of ROS, which activates the inflammasome. Interestingly, Dai et al 36 reported that administration of cyclosporin A protects AAA expansion in the rat elastase and murine calcium chloride models in vivo. Although molecular link between mitochondrial dysfunction and inflammasome activation remains to be determined, these data suggest the critical role of mitochondria-dependent NLRP3 inflammasome activation in progression of AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with NaCl-treated mice, perivascular application of CaCl 2 to the infrarenal abdominal aorta induced a significant increase of the external aortic diameter from day 2 to day 14 after surgery, with a maximum dilatation reaching 150±19% at day 14 ( Figure 1B), in accordance with previous data. 15 The level of SDF-1α, β, γ, and CXCR4 mRNA increased significantly in mouse aortas after CaCl 2 aneurysmal induction, as early as day 2 and up to day 14 ( Figure 1C). A positive correlation between aortic mRNA content and aortic diameter was only demonstrated for the SDF-1a isoform and CXCR4 transcripts ( Figure 1D).…”
Section: Sdf-1/cxcr4 Axis Is Upregulated In Human and Experimental Aaasmentioning
confidence: 92%
“…These data are supported by similar findings from other studies showing inflammatory cell infiltration in the absence of TGF-β1. 10,11,48 Recently, Dai et al 9 showed that Cyclosporine A induced TGF-β1 in samples of human AAAs in vitro and in animal models of AAA in vivo. Administration of Cyclosporine A for 7 days stabilized already formed AAAs with concomitant downregulation of vascular wall inflammation, suggesting that pharmacological induction of TGF-β1 is a potential approach to induce AAA stabilization.…”
Section: Downloaded Frommentioning
confidence: 99%
“…quantification of atherosclerosis by en face staining is a rapid method [9,10]. Hence 135 atherosclerosis was determined in the aortic arch by Sudan IV staining as described 136 previously [1].…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation